2019
DOI: 10.3390/cancers11101421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibroblast-Derived SPARC on Invasiveness of Colorectal Cancer Cells

Abstract: Secreted protein acidic and rich in cysteine (SPARC) is a matricellular protein modulating cell-matrix interactions and was found up-regulated in tumor stroma. To explore the effect of high stromal SPARC on colorectal cancer (CRC) cell behavior and clinical outcome, this study determined SPARC expression in patients suffering from stage II and III CRC using a publicly available mRNA data set and immunohistochemistry of tissue microarray sections. Moreover, in vitro co-culture models using CRC cell lines togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…It has been reported that JMJD5 was important for sustaining cell migration and invasion, and could be a potential oncogene for colon carcinogenesis [42]. SPARC is highly expressed in many tumors, and a research showed that its expression is related with metastasis and recurrence of colon cancer [43,44]. CTGF has shown to be associated with progression, tumorigenesis, and prognosis of various cancers [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that JMJD5 was important for sustaining cell migration and invasion, and could be a potential oncogene for colon carcinogenesis [42]. SPARC is highly expressed in many tumors, and a research showed that its expression is related with metastasis and recurrence of colon cancer [43,44]. CTGF has shown to be associated with progression, tumorigenesis, and prognosis of various cancers [45,46].…”
Section: Discussionmentioning
confidence: 99%
“… 24 SPARC expression was decreased in PCa cell lines because of hypermethylation of the SPARC promoter, and SPARC hypermethylation was correlated with a poorer prognosis in PCa patients. 25 In colorectal cancer (CRC), high stromal SPARC indicated poor prognosis in CRC patients, and fibroblast-derived SPARC enhanced tumor cell invasion; 26 however, other studies revealed that low expression of SPARC in CRC tissue is associated with poor prognosis and aggressive clinicopathological features. 27 , 28 In studying the relationship between SPARC and gynecological tumors, we also found contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The components of the desmoplastic stroma, such as type I collagen, have been described to enhance proliferation of PDAC cells [ 5 ], to increase invasion of tumor cells and to contribute to drug resistance by increasing expression of membrane-type 1 matrix metalloproteinase (MT1-MMP) [ 6 , 7 ]. The tumor-promoting effects of the tumor stroma was not exclusively shown for PDAC, but also for other cancers, such as lung or colon cancer [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%